Spirituality and Life Satisfaction in Pediatric Hematology/Oncology Healthcare Professionals - Hüseyin Çaksen (Pakistan Journal of Medical & Health Sciences, 2023)
Spirituality in its general meaning is the quality or state of being spiritual or being attached to questions and values concerned with religion. It is also frequently used in a non-religious sense to designate a capacity to understand fundamental moral and existential questions regarding the nature of soul1. Religion and spirituality are becoming increasingly important in the care of seriously ill patients2. Life satisfaction is the way in which people show their emotions, feelings (moods) and how they feel about their directions and options for the future3. Here, we presented our observations about spirituality and life satisfaction in pediatric hematology/oncology healthcare professionals to draw attention to the spiritual aspects of health professionals.